Pengaruh Self Efficacy Dan Disiplin Kerja Terhadap Kinerja Personel Sat Intelkam Polda Jatim Yang Dimediasi Oleh Promosi Jabatan - Hartono Hartono; Yoni Evan Pratama; Adinda Jennifer P; Donny Melianto; Siti Mujanah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study is entitled the influence of self-efficacy and work discipline on the performance of personnel of the East Java Regional Police Intelkam Unit mediated by Job Promotion. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 80 respondents. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe self-efficacy, work discipline, job promotion, and personnel performance at the East Java Regional Police Intelkam Unit. 2) To test and analyze whether there is a significant influence of self-efficacy on personnel performance at the East Java Regional Police Intelkam Unit. 3) To test and analyze whether there is a significant influence of work discipline on personnel performance at the East Java Regional Police Intelkam Unit. 4) To test and analyze whether there is a significant influence of job promotion on personnel performance at the East Java Regional Police Intelkam Unit. 5) To test and analyze whether there is a significant influence of self-efficacy on job promotion at the East Java Regional Police Intelkam Unit. 6) To test and analyze whether there is a significant influence of work discipline on job promotion at the Sat Intelkam Polda Jatim. 7) To test and analyze whether there is a significant indirect influence of self efficacy on personnel performance at the Sat Intelkam Polda Jatim with job promotion as an intervening variable. 8) To test and analyze whether there is a significant indirect influence of work discipline on personnel performance at the Sat Intelkam Polda Jatim with job promotion as an intervening variable. The research results show that: 1) self efficacy has a positive insignificant effect on personnel performance. 2) Work discipline has a positive significant effect on personnel performance. 3) job promotion has a positive significant effect on personnel performance. 4) self efficacy has a positive insignificant effect on job promotion. 5) work discipline has a positive significant effect on job promotion. 6) self efficacy on personnel performance through job promotion has a significant positive effect. 7) work discipline on personnel performance through job promotion has a significant positive effect.